A Study On The Factors Influencing The Success Of Statistical Process Control (SPC) Projects In Electrical And Electronics Firms - Siea Dass, Phynthamilkumaran (2007)

(untitled)
Kajian ini mengkaji faktor-faktor utama yang mempengaruhi kejayaan pelaksanaan Kawalan Proses Statistik (SPC) di firma-firma elektrik dan elektronik di sekitar kawasan perindustrian Pulau Pinang and Kulim. Hubung-kait di antara pembolehubah pengantara dengan perubahan budaya turut dikaji. Borang soal-selidik diedarkan kepada responden kajian melalui Jabatan Sumber Manusia dan Jabatan Kualiti di syarikat-syarikat pemilikan Jepun, Amerika, Eropah serta Malaysia. Kaedah persampelan bertujuan digunakan bagi mengumpul data daripada mereka yang pemah terlibat dalam pelaksanaan dan pengamalan projek-projek SPC. Sejumlah 160 borang soal-selidik diedarkan untuk pengumpulan data. This study exammes the key factors influencing success of implementing Statistical Process Control (SPC) in Electrical and Electronics firms in Penang and Kulim Industrial area. The relationship between the moderating variable, culture change is also being studied. Questionnaire was distributed to the respondents by the Human Resource department and Quality Assurance department in each selected Japanese, American, European and Malaysian ownership of companies. Purposive sampling method was used to collect the data from those who have experience in implementing and practicing SPC projects. Total of 160 questionnaires were distributed. It is done to prevent any noise factor in the data.